Assimilating aircraft-based measurements to improve forecast accuracy of volcanic ash transport. (August 2015) - Fu, G.; Lin, H.X.; Heemink, A.W.; Segers, A.J.; Lu, S.; Palsson, T.
Abstract: The 2010 Eyjafjallajökull volcano eruption had serious consequences to civil aviation. This has initiated a lot of research on volcanic ash transport forecast in recent years. For forecasting the volcanic ash transport after eruption onset, a volcanic ash transport and diffusion model (VATDM) needs to be run with Eruption Source Parameters (ESP) such as plume height and mass eruption rate as input, and with data assimilation techniques to continuously improve the initial conditions of the forecast. Reliable and accurate ash measurements are crucial for providing a successful ash clouds advice. In this paper, simulated aircraft-based measurements, as one type of volcanic ash measurements, will be assimilated into a transport model to identify the potential benefit of this kind of observations in an assimilation system. The results show assimilating aircraft-based measurements can significantly improve the state of ash clouds, and further providing an improved forecast as aviation advice. We also show that for advice of aeroplane flying level, aircraft-based measurements should be preferably taken from this level to obtain the best performance on it. Furthermore it is shown that in order to make an acceptable advice for aviation decision makers, accurate knowledge about uncertainties of ESPs and measurements is of great importance. Highlights: Aircraft-based measurements are assimilated into a volcanic ash transport model. Assimilation can significantly improve the state of ash clouds and ash forecast. Measurements should be preferably taken from the same level with aeroplane flying. Uncertainty knowledge of ESPs and measurements is important for aviation advice.